2023
DOI: 10.3389/fmicb.2023.1055804
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of studies on gut microbiota in attention-deficit and hyperactivity disorder from 2012 to 2021

Abstract: BackgroundAn increasing number of studies have focused on the role of gut microbiota in the treatment of ADHD, but its related molecular mechanisms are not yet clear, and there is still room for development of studies targeting this area. This study analyzes publications from 2012 to 2021 in a comprehensive and multi-faceted visualization, with the aim of grasping the existing research profile and guiding scholars to make more in-depth studies.MethodsThe 1,677 articles and 298 review articles on gut microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Keywords were selected according to the search within Medical Subject Headings (MeSH) in PubMed or from previous bibliometric studies [ 57 62 ] or meta-analysis and systematic studies [ 3 , 63 – 67 ]. The results were filtered by limiting documents to journal research, while proceedings, conferences, books, and book chapters were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Keywords were selected according to the search within Medical Subject Headings (MeSH) in PubMed or from previous bibliometric studies [ 57 62 ] or meta-analysis and systematic studies [ 3 , 63 – 67 ]. The results were filtered by limiting documents to journal research, while proceedings, conferences, books, and book chapters were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The interpretation of research and scientific discoveries related to RCTs involving gut microbiota is not fully studied. However, ongoing research in this area will probably persist, as suggested by studies that are akin to those centered on microbiota[ 20 - 22 ], including investigations into the role of the gut microbiota in schizophrenia[ 23 ], nutrition[ 24 ], bone metabolism[ 25 ], cardiovascular diseases[ 26 - 28 ], atherosclerosis[ 29 ], diabetes (both type 1 and type 2)[ 30 , 31 ], irritable bowel syndrome[ 32 , 33 ], depression[ 34 ], autoimmune diseases[ 35 ], rheumatoid arthritis[ 36 ], attention deficit and hyperactivity disorder[ 37 ], cancer[ 38 - 42 ], the microbiome-gut-brain axis[ 38 - 42 ], and fecal microbiota transplantation[ 43 - 47 ].…”
Section: Introductionmentioning
confidence: 99%